Novel unbiased DARTS approach to find protein targets for endophyte extracts in a selected number of cancer cell lines - Alghamdi, Badria Mohammed; Alnakadi, Yasser (Journal of medical and pharmaceutical sciences, 2020)
Background: DARTS "Drug Affinity Responsive Target Stability" is a novel methodology for identifying and studying protein-ligand interactions. This technique depends on the reduction in the protease susceptibility of the target protein upon drug binding. Objectives: The aim of this study to prove the effectiveness of the method to identify the molecular target proteins of some bioactive endophyte extracts. The basic idea of this research is studying the possibility of the use of Darts technique for the detection of cellular targets for natural extracts before doing chemically analyzed to determine the type of vehicle which they are located. Methodology: To achieve the aim of study, some natural extracts of fungi endophyte were selected for the study, three of which are able to stop the growth of three kinds of cancer cells leukemia and lung cancer and cervical cancer, as demonstrated by tests performed in this study. Results: Then Darts technique was used to identify the cellular targets of these extracts successfully. Possible, as already identified a number of proteins that interact with these extracts within the cell. It was possible for first time by using DARTS followed by MALDI-TOF analysis and peptide mass fingerprinting to identify a number of cellular target molecules for bioactive extracts of endophytes. Conclusion: This will help reduce the number of extracts that go into the process of drug development because the extracts which is not suitable to be excluded from the start without the need to chemically analyzed to determine composition, which helps to reduce the cost and the time period required by the process of drug development in the future. This opens up a new area for the use of this technique in the process of scanning cytometry initial natural extracts without having to analyze it chemically which reduces the effort and expense. Finally, A number of very interesting proteins could be identified that might stimulate the researchers in a future study to the chemical composition of these extracts to exactly identify the active component in each of them.